Differences in Painting Styles of Malaysian Chinese Artists in Different Periods - Geng, Wenyan; W Mohamad Daud, Wan Samiati Andriana; Tahir, Azian; Li, Jie (Environment-Behaviour Proceedings Journal, 2024)
Chuah Thean Teng, through continuous experimentation and improvement, has upgraded Batik from a traditional craft to an artwork with cultural significance and national characteristics. His son and grandson are also trying to develop batik painting. The primary purpose of this study is to explore the batik works of artists from different periods. The results show that from the first to the third generation of Chinese artists, their creations have gradually pursued stylistic diversity from their original focus on cultural significance. This study contributes to the dissemination of batik art.